The SDG and the perspective of education for sustainability in the PPC’s of undergraduate biology courses in the Amazon region of Pará - Silva, Natanael Charles da; Araújo, Magnólia Fernandes Florêncio de (Sustainability in Debate, 2022)
The objective of this research was to identify the presence of Sustainable Development Goals (SDGs) in the Educational Programs (EPs) of undergraduate biology courses in the Amazon region of Pará, as well as to characterise the approach these documents take to education for sustainability. Both quantitative and qualitative document analyses were carried out, which identified that five of the 17 SDGs are present in all EPs, two were not found in any of them, and another three were present in 80% of the documents. Although they do not explicitly explore the SDGs and the concept of education for sustainability, some documents carry similarities with this perspective, as they point to the need for training professionals with socio-environmental responsibility. The research presents practical contributions, both from scientific and social points of view, which can be used in documents’ guidelines and necessary actions for executing undergraduate courses coherently with the principles of education for sustainability.